Insulin resistance as a systemic player in renal pathology: a review - Igor Adamovich Tyuzikov (Endocrinology Research Centre, 2014)
Current review provides a multifaceted analysis of epidemiological, clinical and experimental evidence for insulin resistance as a systemic player in the development of renal pathology. We discuss both established and potential mechanisms for this effect. Aside from being a marker for glycemic disorders, insulin resistance was shown to be an independent predictor of renal pathology, including such chronic conditions as urolithiasis, renal cysts and malignant renal neoplasms. Early detection and correction of insulin resistance is a promising approach to diagnostics, treatment and prevention of renal pathology.